Long‐term effects of weight‐reducing diets in people with hypertension - Semlitsch, Thomas (Cochrane Database Syst Rev, 2021)
BACKGROUND: All major guidelines for antihypertensive therapy recommend weight loss. Dietary interventions that aim to reduce body weight might therefore be a useful intervention to reduce blood pressure and adverse cardiovascular events associated with hypertension. OBJECTIVES: Primary objectives To assess the long‐term effects of weight‐reducing diets in people with hypertension on all‐cause mortality, cardiovascular morbidity, and adverse events (including total serious adverse events, withdrawal due to adverse events, and total non‐serious adverse events). Secondary objectives To assess the long‐term effects of weight‐reducing diets in people with hypertension on change from baseline in systolic blood pressure, change from baseline in diastolic blood pressure, and body weight reduction. SEARCH METHODS: For this updated review, the Cochrane Hypertension Information Specialist searched the following databases for randomised controlled trials up to April 2020: the Cochrane Hypertension Specialised Register, CENTRAL (2020, Issue 3), Ovid MEDLINE, Ovid Embase, and ClinicalTrials.gov. We also contacted authors of relevant papers about further published and unpublished work. The searches had no language restrictions. SELECTION CRITERIA: We included randomised controlled trials (RCTs) of at least 24 weeks' duration that compared weight‐reducing dietary interventions to no dietary intervention in adults with primary hypertension. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed risks of bias and extracted data. Where appropriate and in the absence of significant heterogeneity between studies (P > 0.1), we pooled studies using a fixed‐effect meta‐analysis. In case of moderate or larger heterogeneity as measured by Higgins I(2), we used a random‐effects model. MAIN RESULTS: This second review update did not reveal any new trials, so the number of included trials remains the same: eight RCTs involving a total of 2100 participants with high blood pressure and a mean age of 45 to 66 years. Mean treatment duration was 6 to 36 months. We judged the risks of bias as unclear or high for all but two trials. No study included mortality as a predefined outcome. One RCT evaluated the effects of dietary weight loss on a combined endpoint consisting of the necessity of reinstating antihypertensive therapy and severe cardiovascular complications. In this RCT, weight‐reducing diet lowered the endpoint compared to no diet: hazard ratio 0.70 (95% confidence interval (CI) 0.57 to 0.87). None of the trials evaluated adverse events as designated in our protocol. The certainty of the evidence was low for a blood pressure reduction in participants assigned to weight‐loss diets as compared to controls: systolic blood pressure: mean difference (MD) −4.5 mm Hg (95% CI −7.2 to −1.8 mm Hg) (3 studies, 731 participants), and diastolic blood pressure: MD −3.2 mm Hg (95% CI −4.8 to −1.5 mm Hg) (3 studies, 731 participants). We judged the certainty of the evidence to be high for weight reduction in dietary weight loss groups as compared to controls: MD −4.0 kg (95% CI −4.8 to −3.2) (5 trials, 880 participants). Two trials used withdrawal of antihypertensive medication as their primary outcome. Even though we did not consider this a relevant outcome for our review, the results of these RCTs strengthen the finding of a reduction of blood pressure by dietary weight‐loss interventions. AUTHORS' CONCLUSIONS: In this second update, the conclusions remain unchanged, as we found no new trials. In people with primary hypertension, weight‐loss diets reduced body weight and blood pressure, but the magnitude of the effects are uncertain due to the small number of participants and studies included in the analyses. Whether weight loss reduces mortality and morbidity is unknown. No useful information on adverse effects was reported in the relevant trials.